A new species of Holocephalus Hope from Paraguay (Coleoptera: Scarabaeidae: Scarabaeinae: Dichotomiini s. str.) - Nunes, Rafael V.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2016)
It came to us from Svatopluk Pokorný a single Scarabaeinae specimen from Paraguay which we promptly diagnosed as belonging to the genus Holocephalus Hope, mainly due to the shape of first labial palpomere, head, cephalic carina, pronotum and other secondary charateristics (Smith & Génier 2001, Vaz-de-Mello et al. 2011). Comparisons with the diagnosis provided in the very fine and comprehensive revision of the genus (Smith & Génier 2001) and with specimens deposited at CEMT (Cuiabá-MT, Brazil) allowed us to confirm that this exemplar belongs to a new species of Holocephalus, which is described here. Besides providing illustrated description and diagnosis of the sixth discovered species of the genus, we differentiate it in a Holocephalus key adapted from Smith & Génier (2001) and also provide additional geographical records for other species in the genus.